Purifying the 1920s Southern American Society: The Grotesque in Flannery O’Connor’s “A Good Man is Hard to Find” - Dian Windriani (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2018)
Flannery O’Connor’s “A Good Man is Hard to Find” (1953) criticizes the experience of hu- man’s isolation, vanity, and disillusionment in Southern America under political instability, dic- tatorial regime, hypocrisy of the church and high number of poverty that can lead to the crisis of faith and humanity in people’s life. By presenting the violence, horror, and emotional freak in the story, O’Connor wishes that the characters can come to their self-realization upon their faith and humanity. This paper finds out that the portrayal of grotesque character in “A Good Man is Hard to Find” can be seen as a mechanism to purify the Southern American society in the twen- tieth century that has already been far away from their religious belief.